Midwives Complience, Mother And Child Health Book, And Mother’s Health - Fitnaningsih Endang Cahyawati; Septiana Nurmalitasari (International Journal of Health Science and Technology, 2020)
The Maternal and Child Health Book (MCH Handbook) contains maternal (pregnant, childbirth and postpartum) health records and children (newborns to 6 year old children) as well as various information on how to maintain and care for the health of mothers and children. Based on the 2012 Indonesia Demographic Health Survey (IDHS), the maternal mortality rate (related to pregnancy, childbirth and childbirth) was 359 per 100,000 live births. This study aims to determine the compliance of the MCH handbook by midwives in early detection of high risk of pregnancy in the Kasihan 1 Health Center, Bantul Regency. This study used a descriptive quantitative research design. The variable in this study consisted of one variable, namely compliance with the book of MCH handbook by Midwife in early detection of high risk of pregnancy. The sampling technique in this study was total sampling, with a sample of 9 midwives. The results showed that the compliance of midwives in completing MCH handbooks at the Puskesmas Kasihan 1 Bantul District was mostly obedient with 6 KIA midwives with a percentage of 66.7% and not complying with 3 midwives with a percentage of 33.3%. The suitability of midwives in filling MCH books at the Puskesmas Kasihan 1 Bantul Regency was mostly according to 41 MCH books with a percentage of 68.3% and not according to 19 MCH books with a percentage of 31.7%. The next researcher is expected to be able to conduct a complete research thoroughly the factors that influence the completeness of the MCH handbook by observing and interviewing midwives.